Методологічні засади організації обліку інвестиційної нерухомості: компаративний аналіз НП(С)БО 32 та IAS 40 - Шеверя, Ярослав Вікторович; Ганусич, Вероніка Олександрівна; Sheveria, Yaroslav; Hanusych, Veronika (Запоріжжя : Видавничий дім «Гельветика», 2026)
UA: У статті здійснено компаративний аналіз методологічних засад організації обліку інвестиційної нерухомості відповідно до НП(С)БО 32 та IAS 40. Досліджено критерії ідентифікації об’єктів, підходи до первісної та подальшої оцінки, особливості застосування моделей справедливої вартості й собівартості, а також порядок нарахування амортизації. Виявлено концептуальні відмінності у трактуванні об’єктів нерухомості змішаного використання та механізмах визначення справедливої вартості. Обґрунтовано напрями гармонізації національного регулювання з міжнародними стандартами через уточнення критеріїв класифікації інвестиційної нерухомості, удосконалення підходів до визначення справедливої вартості та підвищення ролі професійного судження, орієнтацію на принцип превалювання економічної сутності над юридичною формою, що сприятиме підвищенню порівнянності, достовірності та інвестиційної привабливості фінансової звітності українських підприємств. /// EN: The article examines the methodological foundations of accounting for investment property through a comparative analysis of National Accounting Standard 32 “Investment Property” and IAS 40 “Investment Property.” The study substantiates that the Ukrainian regulation is conceptually aligned with the international model; however, certain methodological distinctions remain in the interpretation of classification criteria, mixed-use property, fair value measurement mechanisms and the recognition of changes in value. Particular attention is devoted to the identification criteria of investment property based on its economic purpose and the autonomy of cash flows, as well as to the recognition of right-of-use assets in accordance with the substance-over-form principle embedded in IAS 40. The paper provides a structured comparison of initial and subsequent measurement models, including the cost model and the fair value model, and highlights differences in disclosure requirements and the treatment of revaluation effects. The fair value measurement framework is analysed in connection with IFRS 13, emphasizing the hierarchy of inputs and valuation approaches, while the national methodology is characterized as more formalized and rule-based. The research demonstrates that although the regulatory frameworks are generally harmonized, further conceptual integration is required, particularly regarding professional judgement, market-based valuation infrastructure and transparency of financial reporting. The directions for harmonising national regulation with international standards have been substantiated by clarifying the criteria for classifying investment property, improving approaches to determining fair value and increasing the role of professional judgement, and focusing on the principle of economic substance over legal form, which will contribute to improving the comparability, reliability and investment attractiveness of the financial statements of Ukrainian enterprises. The findings contribute to a deeper understanding of methodological convergence between national and international standards and outline directions for improving the accounting framework of investment property in Ukraine in line with global best practices.
Methodological foundations of the organization of investment property accounting: a comparative analysis of National Accounting Standard 32 and IAS 40
Keywords: інвестиційна нерухомість; справедлива вартість; модель собівартості; гармонізація стандартів; компаративний аналіз; професійне судження; міжнародні стандарти фінансової звітності; investment property; fair value; cost model; harmonization of standards; comparative analysis; professional judgement; International Financial Reporting Standards